Beauty Worth Sharing: An Introduction to Koinon VI, with Recourse to Marlaina - Molinari, Dr. Nicholas J. (KOINON: The International Journal of Classical Numismatic Studies, 2023)
Numismatics, especially Classical Numismatics, is chock-full of beautiful surprises worth sharing. Every day I learn something new, and as a community we all relish in what seems to be a daily revelation of novel discoveries. But I’ve come to the conclusion recently that numismatists themselves are just as interesting, in fact even moreso than the coins we all cherish. Fairly recently I met one such numismatist: Her name is Marlaina and it would be a rare occasion to find her without a bag of coins—yes, she keeps them all in a small bag resembling a pencil case, where they are constantly rubbing against each other! Marlaina has been a collector as long as I have (nearly twenty years), and although she mostly collects United States and Canadian coinage, she certainly has a fair share of World coins and even a few ancients. Her favorite numismatic objects, however, are tokens—turnpike tokens, tokens from restaurants, Alcoholics Anonymous tokens, etc. Among these one stands out: a token from McDonalds, which sits in her bag alongside various silver dollars, large cents, and the rest of her treasure. But it isn’t Marlaina’s eclectic collection that makes Marlaina so special, or the fact that she may be the only numismatist that carries the majority of her coins in a bag. The most suprising thing about Marlaina is that she has never seen a coin—Marlaina is completely blind